Plant cell walls : from chemistry to biology - Albersheim, Peter (Garland Science, 2011)
Plant cell walls are complex, dynamic cellular structures essential for plant growth, development, physiology and adaptation. This text provides a view of the microanatomy, biosynthesis and molecular physiology of these cellular structures, both in the life of the plant and in their use for bioproducts and biofuels.